Access to Primary Care and Mental Health Care in Renfrew County - Belanger, Christopher; Fitzsimon, Jonathan; Bjerre, Lise M. (Université d'Ottawa | University of Ottawa, 2021)
This report presents a geostatistical analysis of access to primary care, adult and child/youth mental health care, and broadband internet services in Renfrew County, Ontario. We located and mapped primary-care and mental-health providers within and near Renfrew County, and calculated the average travel burden to access these providers within each of Renfrew County’s 19 census subdivisions. The analysis found strong evidence that Renfrew County’s residents face urban/rural disparities in access to both primary care and mental health care. We found that care providers are largely located in urban areas, and that, on average urban residents have much shorter travel times to access care than rural residents. In some cases, rural residents of Renfrew County can need to travel over twenty times longer than urban residents to access care. The situation was similar for mental health services, both for adults and for children and youth. We also found that much of Renfrew County has good access to wired broadband networks. Coverage tended to be better in regions with better health care access, including urban centres along the Highway 17 corridor, but there was also coverage in some rural areas. Taken together, this suggests that telemedicine services could play an important role in increasing access to health care in Renfrew County. Since telemedicine services are provided over the internet, travel times and physical distance are irrelevant. Residents in parts of Renfrew County with long average travel times and few local providers could therefore benefit greatly from telemedicine, and this analysis suggests that many residents in these regions have at least some broadband access.
Keywords: Primary Care; Mental Health; Virtual Care; Telemedicine; Travel burden; Geospatial mapping; Access